The correlation between plastic strain and anisotopy strain in aluminium alloy polycrystals - Korsunsky, A; Daymond, M; James, K (Elsevier, 2002)
Samples of fine-grained Al alloy reinforced with SiC particles were subjected to in situ deformation in four-point bending, and multiple-peak diffraction patterns were collected along a line traversing the sample bend axis, using time-of-flight neutron diffraction at the ISIS pulsed source, at the Rutherford Appleton Laboratory, Oxford. The patterns were analysed in order to determine the average macroscopic lattice (elastic) strain, and also the so-called anisotropy strain. It was assumed that the deformation condition in the sample corresponded to a simple uniaxial stress state, and that the entire composite plastic strain was accommodated by matrix plasticity. This allowed comparisons to be made with the prediction of some models, namely, a simple two-phase uniform strain (Voigt) model, and an elasto-plastic self-consistent polycrystalline deformation model. A direct correlation is observed between the matrix plastic strain and the anisotropy strain determined from the diffraction spectra.